Film Animasi sebagai Pembelajaran Practical Life untuk Meningkatkan Kemandirian Anak Usia Dini - Kolbiah, Lutfi; Rohmalina, Rohmalina (IKIP Siliwangi, 2024)
The ability of independence in early childhood education is a demand at this time, where this ability of independence is needed by early childhood to be able to survive and be able to mingle in an even bigger environment compared to the family environment, namely the community environment. Besides that, in stimulating independence abilities, the teacher's efforts are also needed in presenting interesting learning of independence skills so that children do not feel burdened, media that is interesting and fun for children is needed. Therefore this study aims to increase the independence abilities of group A children, namely children aged 4-5 years by learning practical life through animated films. This research method uses descriptive qualitative research with descriptive data analysis. The subjects of this study were 8 children in group A at RA Arafah Cimahi Selatan and data collection techniques were through observation and documentation. Based on the results of this study, it shows that there is an increase in the ability of independence in group A children by learning practical life through animated films. Obtained the final results of the study of 8 research subjects 1 child whose independence ability began to develop and 7 children's independence ability has developed very well